SUPPLY CHAIN PERFORMANCE MEASUREMENT AND PRODUCTIVITY IN EDUCATIONAL CAREER ASSISTANCE (CAREER DEVELOPMENT OF EDUCATIONAL PERSONNEL IN JAMBI UNIVERSITY) - Firman, Firman; Murboyono, Rahmat; Anra, Yusdi (International Journal of Supply Chain Management, 2019)
Human resource management for the supply chains is recognized increasingly important for its role to fulfill the demands of work or position as a result of advances in science and technology and increasingly intense competition among similar organizations or institutions. Each employee is required to be able to work effectively and efficiently in completing work, and is able to show the quality and quantity of good work in order to develop the competitiveness of the organization. With regard to the issue, this study was carried out by using a quantitative associative approach with survey methods and applied path analysis and regression technique to test the directly and indirectly effect on each research variable. Furthermore, this study involved educational staff of Jambi University as the respondents of the study in human resource management. Based on the research approach, it was expected to produce a career development model to support the performance in giving excellent service to the community in Jambi University. The result of the study noted and emphasized that there was the effect of working climate on organizational culture as 11.3, working motivation on organizational culture as 12.4, working climate on career development as 41.7, working motivation for career development as 15.4, organizational culture on career development as 12.6, working climate on career development through organizational culture as 43.8, and working motivation on career development through organizational culture as 20.8. The result indicated that to increase working climate, working motivation and supply chai management should be increased, too. In other words, to improve career development, it can be achieved by improving the variables of those three variables; working climate, working motivation, and organizational culture.